Neuroregulation of the Hypothalamus-Pituitary-Adrenal (HPA) Axis in Humans: Effects of GABA-, Mineralocorticoid-, and GH-Secretagogue-Receptor Modulation - Roberta Giordano; Micaela Pellegrino; Andreea Picu; Lorenza Bonelli; Marcella Balbo; Rita Berardelli; Fabio Lanfranco; Ezio Ghigo (The Scientific World Journal)
The hypothalamus-pituitary-adrenal (HPA) axis exerts a variety of effects at both the central and peripheral level. Its activity is mainly regulated by CRH, AVP, and the glucocorticoid-mediated feedback action. Moreover, many neurotransmitters and neuropeptides influence HPA axis activity by acting at the hypothalamic and/or suprahypothalamic level. Among them, GABA and Growth Hormone Secretagogues (GHS)/GHS-receptor systems have been shown to exert a clear inhibitory and stimulatory effect, respectively, on corticotroph secretion. Alprazolam (ALP), a GABA-A receptor agonist, shows the most marked inhibitory effect on both spontaneous and stimulated HPA axis activity, in agreement with its peculiar efficacy in panic disorders and depression where an HPA axis hyperactivation is generally present. Ghrelin and synthetic GHS possess a marked ACTH/cortisol-releasing effect in humans and the ghrelin/GHS-R system is probably involved in the modulation of the HPA response to stress and nutritional/metabolic variations. The glucocorticoid-mediated negative feedback action is mediated by both glucocorticoid (GR) and mineralocorticoid (MR) receptors activation at the central level, mainly in the hippocampus. In agreement with animal studies, MRs seem to play a crucial role in the maintenance of the circadian ACTH and cortisol rhythm, through the modulation of CRH and AVP release. GABA agonists (mainly ALP), ghrelin, as well as MR agonists/antagonists, may represent good tools to explore the activity of the HPA axis in both physiological conditions and pathological states characterized by an impaired control of the corticotroph function.